Regional Action Programme (RAP): networking activities 1998-2000 - Hamdy A.; Lamaddalena N.; Steduto P. (Regional Action Programme (RAP): Water resources management and water saving in irrigated agriculture (WASIA PROJECT), 2003)
Regional Action Programme (RAP): networking activities 1998-2000